Handling of Murabahah Financing for Customers who Die before The Date - Martega Maruf Walinten; Satrio Agung Wicaksono; Adnan Cahyo Pamungkas; Bobo Alex Sandro; Karisma Arum Aprilia; Fanesa Amanda (Universitas Muhammadiyah Surakarta, 2023)
In Islamic banking there is a murabahah system in which the system uses buying and selling instruments by taking advantage. Where the murabahah is used as another option for customers to solve financial problems when they have difficulty buying an item. Islamic banking takes murabahah efforts with the aim of providing short-term financing to customers to obtain goods even though the customer does not have enough money to make payments. The purpose of this research was to find a way to do so murabaha settlement efforts are for customers who die before maturity. The impact of murabahah for the customer who dies is that the debt is borne by the heirs of the customer.